Desenvolvimento de aplicativo para dispositivos móveis de mensuração de injestão proteica diária por pessoas idosas - (:unkn) unknown (Universidade Brasil, 2022)
Technology is part of the daily life, and the ageing population will expand its use by the elderly people for several purposes, health care for example. Nutrition in geriatrics is gaining increasing relevance, in particular, the goals of protein ingestion, that have been increasing recently. Therefore, mobile apps can be used to track inadequacies in this regard. This research aimed to develop an app that performs a 24-hour food diary by the elderly user, in an automated way, submitting it to quality tests and usabilityvalidation. It was developed with a focus on the specificities of this group and subjectedto quality tests in an exhausting way. The usability was evaluated in two stages: Stage1(N=8) -central group discussion, which took place before the elaboration of its finalversion, including elderly users in the development process; and Stage 2 (N = 18) -evaluation by elderly participants who did not have cognitive decline identified by the10-point cognitive screening tool (10-CS), using the System Usability Scale (SUS scale). The final version of the PROT+ app for Android, obtained after quality tests andproposals made by the focused discussion group, presented screens for simple andintuitive use, and a tutorial video to guide the user. Data from the SUS scale performedby 16 participants, were analyzed by groups divided by schooling and age range. The average of the groups with schooling from zero to four years, five to 11 years, andhigher than or equal to 12 formal years of study were 80 (Interquartile Range (IQR) 48.13), 95 (IQR 15) and 92.5 (IQR 10), respectively. And for age range from 60 to 69 years old, 70 to 79 years old, and over 80 years old, were 95 (IQR 8.75), 85 (IQR33.75), and 87.5 (IQR 10), respectively. There were no differences in usability betweenthe groups by schooling, but there was a large difference between the 60-69 and 70-79 age groups. However, all averages were higher than the scores of other applicationsdeveloped for elderly users and satisfactory by the SUS scale. Therefore, the PROT+app is a geriatric nutritional tool, which is easy to use, with an interface adapted to the specificity of its target audience and demonstrated satisfactory performance in allrequirements evaluated after functional and non-functional quality tests, as well as usability.
Keywords: Aplicativo; Proteína; Pessoa idosa; Recordatório alimentar 24 horas; Engenharia Biomédica; Bioengenharia